View of the east-facing Mandapa of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
View of the east-facing mandapa (pillared hall) of the Bhandasar Temple. The mandapa has eight main pillars that support the central dome. Beyond this intercolumniation lies the main garbhagriha (sanctum sanctorum) which enshrines Sumatinatha Tirthankara. All the wall and pillar surfaces are painted.